2003
DOI: 10.1046/j.1439-0264.2003.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Cardiac Nerve Segments in the Domestic Dog (Canis familiaris– Linnaeus, 1758). Comparative Study in Young and Adult Dogs

Abstract: In this paper, important connections between the two main contingents of the autonomic nervous system, intrinsic and extrinsic visceral plexus were analysed. Concerning heart innervation, the territories of extrinsic innervation are very important in the treatment of congenital or acquired cardiopathy, thoracic neoplasia and aortic arch persistence, among others. This research compared young and adult extrinsic cardiac innervation and described the surgical anatomic nerve segments. Animals were perfused with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b). A through understanding of primate morphology is important because the primate ancestor diverged from the ancestor of the rodents, which includes the main experimental animals such as the rat, mouse, and rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b). A through understanding of primate morphology is important because the primate ancestor diverged from the ancestor of the rodents, which includes the main experimental animals such as the rat, mouse, and rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac branches of the vagal nerves can be divided into cranial and caudal cardiac rami Getty, 1969a, 1970;Brugnaro et al, 2003). Studies in domestic small ruminants Getty, 1969a, 1970) documented the existence and involvement of the both cranial and caudal cardiac rami in the cardiac plexus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that both the right and left cardiac plexuses receive extrinsic sympathetic nerves in these animals from the cranial and caudal thoracic cardiac nerves Getty, 1968, 1969a;Brugnaro et al, 2003), the stellate ganglion through the ansa subclavia Getty, 1969b, 1970), and the vertebral and middle cervical ganglia (McKibben and Getty, 1970;Brugnaro et al, 2003). These studies indicated that the paravertebral sympathetic thoracic ganglia caudal to the third one served as the origin for the thoracic cardiac nerves.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, many comparative anatomical studies have been carried out on autonomic cardiac innervation in various vertebrate species, such as the calf (Shaner, 1930), rat (Gómez, 1958;Burkholder et al, 1992;Batulevičius et al, 2004), chick (Kuratani and Tanaka, 1990;Verberne et al, 1998Verberne et al, , 1999, musk shrew (Tanaka et al, 1998), guinea pig (Batulevičius et al, 2005), dog (Randall and Rohse, 1956;Itoh, 1960;Randall et al, 1963Randall et al, , 1968Randall et al, , 1972Randall et al, , 1989Szentivanyi et al, 1967;Randall, 1975, 1985;Norris and Randall, 1977;Rinkema et al, 1982;Armour, 1984, 1989;Brandys et al, 1986;Ardell et al, 1988;Armour, 1988;Gagliardi et al, 1988;Brugnaro et al, 2003), cat (Phillips et al, 1986), and primates (Riegele, 1926;Randall et al, 1971;Billman et al, 1989;Kawashima et al, 2001. Especially, Randall (1975, 1985) contributed to our knowledge of cardiac function using methods such as retrograde tracing and electrophysiology in dogs.…”
mentioning
confidence: 99%